Social Responsibility Scale (SRS-2): Validity Evidence Based on Internal Structure - Otoni, Fernanda (2023)
This study aimed to provide evidence of validity for the Social Responsiveness Scale (SRS-2) based on its internal structure. The results of 1,001 participants, aged between two and 73 years, indicated through Path Analysis that Social Perception predicts 56%, while Social Cognition predicts 79% of social responsiveness, Social Communication 92%, Social Motivation 70%, finally The Social Communication and Social Interaction subscale can predict 96% of social responsiveness. The subscales have a strong correlation magnitude and evidence the contribution of the SRS-2 to assess social responsiveness, in addition to being promising to predict the diagnosis of ASD at the national level.